Mechlorethamine-Induced DNA-Protein Cross-Linking in Human Fibrosarcoma (HT1080) Cells - Michaelson-Richie, Erin D. (2011)
Antitumor nitrogen mustards, such as bis(2-chloroethyl)methylamine (mechlorethamine), are useful chemotherapeutic agents with a long history of clinical application. The antitumor effects of nitrogen mustards are attributed to their ability to induce DNA-DNA and DNA-protein cross-links (DPCs) that block DNA replication. In the present work, a mass spectrometry based methodology was employed to characterize in vivo DNA-protein cross-linking following treatment of human fibrosarcoma (HT1080) cells with cytotoxic concentrations of mechlorethamine. A combination of mass spectrometry-based proteomics and immunological detection was used to identify 38 nuclear proteins which were covalently cross-linked to chromosomal DNA following treatment with mechlorethamine. Isotope dilution HPLC-ESI(+)-MS/MS analysis of total proteolytic digests revealed a concentration-dependent formation of N-[2-(S-cysteinyl)ethyl]-N-[2-(guan-7-yl)ethyl]methylamine (Cys-N7G-EMA) conjugates, indicating that mechlorethamine cross-links cysteine thiols within proteins to N-7 positions of guanine in DNA.